Resiliency and its Relationship with Secondary Traumatic Stress among Nursing Staff during COVID-19 Pandemic - Mahdi Abdolkarimi; Seyedhamid Seyedbagheri; Hamid Ganjeh; Mahmood Kahnooji; Mohammad Ali Zakeri (Journal of Kerman University of Medical Sciences, 2022)
Background: Nurses are front-line health-care workers for patients with severe Coronavirus disease (COVID-19) symptoms. The aim of this study was to determine the resiliency of nurses and its relationship with secondary traumatic stress (STS) in pandemic conditions.Methods: This cross-sectional study was performed on 233 nurses working in a medical center providing services to patients with COVID-19 in southeast Iran from May to August 2020. Data were collected using demographic questionnaire, Connor-Davidson Resilience Scale (CD-RISC) and The Secondary Traumatic Stress Scale (STSS). Pearson correlation coefficient was used to determine the relationship between variables and data were analyzed through SPSS22.Results: The mean STS score of nurses was 40.82 ± 11.7. The results showed a significant relationship between STS score and Job satisfaction. The mean score of resilience was 60.91± 17.1 in nurses. The resiliency score showed significant difference based on work experience and exposure to COVID-19 disease. The results of correlation test showed that the overall stress score was significantly related to all aspects of resilience except trust (p < 0.05).  Also, based on the multiple regression model, positive acceptance (one of the dimensions of resilience) and exposure to COVID-19 disease were the predictors of STS. Conclusion: The results showed that there is a significant and inverse relationship between resiliency score and STS. Therefore, according to the present conditions, it is recommended to design programs to improve resilience and reduce stress of nurses during COVID-19 pandemic.